THE RELATIONSHIP BETWEEN THE USE OF TECHNOLOGY AND THE GENERAL DATA PROTECTION LAW FOR USERS OF FINANCIAL INSTITUTIONS IN THE SÃO PATRÍCIO VALLEY (CIPEEX, 2025)
This study presents the evolution of technology and the importance of the General Data Protection Law (GDPL) for financial institutions Most users appreciate new technologies and the assistance they bring to financial services, and the implementation of GDPL ensures the security of personal data for clients, requiring institutions to apply security measures that preserve data privacy in the digital landscape In order to analyze how users interact with technology in the financial sector, a survey will be conducted in Vale do São Patrício, Goiás The applied methodology will include an electronic questionnaire, based on previous studies, with the aim of collecting data from residents. Through data analysis, it will be possible to identify how customers use the platform and how the GDPL influences the reliability of personal information delivery in the context of a notably technological and integrated era The intention of this research is to provide an in-depth current panorama, revealing consumer behavior regarding technology usage in these institutions As a result, the findings will provide insights to enhance security practices in the financial sector, further strengthening customer trust.
Keywords: technology; general data protection law; security of personal information; financial institutions